Different types of intranasal steroids for chronic rhinosinusitis - Burton, M; Head, K; Chong, L; Hopkins, C; Philpott, C; Schilder, A (Cochrane Collaboration, 2015)
Review question: We reviewed the evidence for the benefits and harms of different types of intranasal (in the nose) steroids given to people with chronic rhinosinusitis. Background: Chronic rhinosinusitis is a common condition that is defined as inflammation of the nose and paranasal sinuses (a group of air-filled spaces behind the nose, eyes and cheeks). Patients with chronic rhinosinusitis experience at least two or more of the following symptoms for at least 12 weeks: blocked nose, discharge from their nose or runny nose, pain or pressure in their face and/or a reduced sense of smell (hyposmia). Some people will also have nasal polyps, which are grape-like swellings of the normal nasal lining inside the nasal passage and sinuses. Topical (intranasal) corticosteroids are used with the aim of reducing inflammation in order to improve patient symptoms. Study characteristics: Different types of intranasal steroids for chronic rhinosinusitis 3 / 68 We included nine randomised controlled trials (RCTs) with a total of 910 participants in this review. The studies varied in size: some were small, with as few as 20 patients, while others included over 200 participants. Most studies recruited adult patients, but one study only included children. In the majority of the adult studies, most participants were male (72% to 79%). In all of the studies the participants had chronic rhinosinusitis with nasal polyps. The studies either compared different types of steroids (three studies), high-dose versus low-dose steroids (five studies), twice daily versus once daily steroids, or different delivery methods (aqueous nasal spray versus aerosol - one study). All of the studies had a placebo group. Key results and quality of the evidence: Different steroids: fluticasone propionate versus beclomethasone dipropionate Two small studies (56 participants, unclear risk of bias) evaluated disease severity and looked at the primary adverse effect, epistaxis (nosebleed), but no other outcomes. No difference was found between the two steroids but we assessed the evidence to be of very low quality. Different steroids: fluticasone propionate versus mometasone furoate One study (100 participants, unclear risk of bias) found no difference in disease severity (nasal symptoms scores). We assessed this evidence to be of very low quality. High-dose versus low-dose steroids We found five studies (663 participants, low or unclear risk of bias) that compared high-dose and low-dose steroids, three using mometasone furoate (400 µg versus 200 µg in adults and older children, 200 µg versus 100 µg in younger children), and two using fluticasone propionate drops (800 µg versus 400 µg). Effectiveness (disease severity and nasal polyps size) was similar between the high-dose and low-dose groups (low quality evidence). Although all studies reported more improvement in polyp score in the high-dose group, the significance of this is unclear because the improvements seen were small. The primary adverse effect, epistaxis, was more common when higher doses were used (moderate quality evidence). Different delivery methods: aqueous nasal spray versus aerosol spray We identified only one poorly reported study with a high risk of bias. It was unclear how many participants there were: 91 were recruited into three arms. There had also been significant differences between the participants in the two groups when they started the study. We were unable to draw any meaningful conclusions from this study. Conclusions: We found no evidence that one type of intranasal steroid is more effective than another in patients with chronic rhinosinusitis, nor that higher doses are better than lower, nor that the effectiveness of a spray differs from an aerosol. We found no studies that compared nasal drops with spray. We did find moderate quality evidence of an increased risk of epistaxis (nosebleed) as an adverse effect of treatment when higher doses were used. More research in this area is clearly needed. In the future studies should be well designed: they should measure chronic rhinosinusitis-specific health-related quality of life and adverse effects as outcomes, and look at what happens to patients taking intranasal steroids in the longer term.